A Role of Corazonin Receptor in Larval-Pupal Transition and Pupariation in the Oriental Fruit Fly Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) - Hou, Qiu-Li; Jiang, Hong-Bo; Gui, Shun-Hua; Chen, Er-Hu; Wei, Dan-Dan; Li, Hui-Min; Wang, Jin-Jun; Smagghe, Guy (Frontiers in Physiology, 2017)
Corazonin (Crz) is a neuropeptide hormone, but also a neuropeptide modulator that is internally released within the CNS, and it has a widespread distribution in insects with diverse physiological functions. Here, we identified and cloned the cDNAs of Bactrocera dorsalis that encode Crz and its receptor CrzR. Mature BdCrz has 11 residues with a unique Ser11 substitution (instead of the typical Asn) and a His in the evolutionary variable position 7. The BdCrzR cDNA encodes a putative protein of 608 amino acids with 7 putative transmembrane domains, typical for the structure of G-protein-coupled receptors. When expressed in Chinese hamster ovary (CHO) cells, the BdCrzR exhibited a high sensitivity and selectivity for Crz (EC50 ≈ 52.5 nM). With qPCR, the developmental stage and tissue-specific expression profiles in B. dorsalis demonstrated that both BdCrz and BdCrzR were highly expressed in the larval stage, and BdCrzR peaked in 2-day-old 3rd-instar larvae, suggesting that the BdCrzR may play an important role in the larval-pupal transition behavior. Immunochemical localization confirmed the production of Crz in the central nervous system (CNS), specifically by a group of three neurons in the dorso-lateral protocerebrum and eight pairs of lateral neurons in the ventral nerve cord. qPCR analysis located the BdCrzR in both the CNS and epitracheal gland, containing the Inka cells. Importantly, dsRNA-BdCrzR-mediated gene-silencing caused a delay in larval-pupal transition and pupariation, and this phenomenon agreed with a delayed expression of tyrosine hydroxylase and dopa-decarboxylase genes. We speculate that CrzR-silencing blocked dopamine synthesis, resulting in the inhibition of pupariation and cuticular melanization. Finally, injection of Crz in head-ligated larvae could rescue the effects. These findings provide a new insight into the roles of Crz signaling pathway components in B. dorsalis and support an important role of CrzR in larval-pupal transition and pupariation behavior.